A review of the common crab genus Macromedaeus Ward, 1942 (Brachyura, Xanthidae) from China Seas with description of a new species using integrative taxonomy methods - Ziming Yuan; Wei Jiang; Zhongli Sha (PeerJ, 2022)
Macromedaeus is one of the most common xanthid genera in shallow waters of the Indo-West Pacific. In this study, we describe a new species, Macromedaeus hainanensis sp. nov., and report on two newly recorded species, M. quinquedentatus (Krauss, 1843) and M. orientalis (Takeda & Miyake, 1969) from Hainan Island, South China Sea. M. hainanensis is most related to M. distinguendus (De Haan, 1833-1850) and M. orientalis on the carapace shape and granular appearance, but can be distinguished by unique morphological characteristics especially its front, pereopods and male first gonopod. Taxonomic identities of the six Macromedaeus species recorded from China seas are discussed, and a phylogenetic analyzation is performed on Macromedaeus and related taxa based on three mitochondrial and two nuclear markers (12S, 16S, COI, H3, 18S). Integrated taxonomic evidence is used to support the taxonomic status of each species.